The karyotype of the indigenous buffalo (Bubalus bubalis) of Sri Lanka - Bongso, Tuan Ariffeen (Ceylon Veterinary Association, 1977)
The somatic chromosomes of the indigenous buffalo in Sri Lanka were studied using the whole blood culture method. A diploid number of 50 was observed which was similar to that found in the River buffalo (Murrah) of Sri Lanka. This report also shows that the karyotype of the Sri Lanka indigenous buffalo is different from that of the Australian and other Asian swamp buffaloes. It is hypothesised that the Sri Lanka indigenous buffalo originated from the River type.